MEMPERKUAT KETAHANAN LINGKUNGAN MELALUI OLAHAN OLI BEKAS PEMBAKARAN KENDARAAN - Suparyogi, Dudi; Hendrawan, Win; Ardianto, Nurmand Bernard; Sodikin, Abdul (JURNAL KEBANGSAAN RI, 2025)
This research aims to design and build a used oil-fueled stove equipped with a steam boiler furnace,which can utilize heat energy to produce steam. The metode use combustion parameters were also analyzed to assess efficiency, flame stability, and emission characteristics. The research results are expected to provide environmentally friendly technological solutions while utilizing waste as a renewable energy source,reducing dependence on fossil fuels, and raising awareness of the importance of sustainable waste management.